More Expensive, More Attractive? The Effect of Pricing on Gift Evaluation: Differences Between Giver and Receiver - Liu, Ning; Lou, Yu; Wang, Xinyu; Li, Shouxin (Frontiers in Psychology, 2022)
The present research explored differences in gift evaluation between gift givers and receivers. Three studies were conducted to test how the pricing influenced the gift evaluations of givers and receivers, and whether the price-quality and price-monetary sacrifice inferences were the underlying mechanisms. The results showed that: givers evaluated high-priced gifts as better than low-priced gifts, whereas receivers evaluated low-priced gifts as better than high-priced gifts; price-quality inference mediated the effect of pricing on gift evaluations, but only for givers. Furthermore, the effect of pricing on gift evaluation was moderated by the gift type: givers evaluated the high-priced gift as better only for the desirable gift (but not for the feasible gift); receivers evaluated the low-priced gift as better only for the feasible gift (but not for the desirable gift). The results demonstrate the effect of pricing on gift evaluation and could contribute to understanding the differences between givers' and receivers' perception of what a "good gift" is, and the underlying psychological mechanisms.